Repeated displacement in eastern DRC - Beytrison, F; Kalis, O (Refugee Studies Centre, University of Oxford, 2013)
For the vast majority of those affected by conflict, displacement is often seen as the only option in an attempt to find safety. The provision of some basic assistance in places to which people flee makes this process slightly easier but in the absence of state-led protection multiple displacement has become a defining feature of the Kivu conflict. This has implications for both the humanitarian and the development response.